Teachers' Perceptions of Motivating Principals' Leadership in Public Junior High Schools - Sukraini, Ade; Ermita, Ermita; Susanti, Lusi; Widiawati, Widiawati (Journal of Educational Management Research, 2025)
This study aims to gather data and information regarding teachers' perceptions of the leadership of the driving principal in State Junior High Schools, focusing on various key aspects. The leadership of the principal is evaluated in terms of teacher development and the improvement of learning quality, effective school management, the creation of a positive school culture, and continuous monitoring and evaluation. Understanding how teachers perceive their principal's leadership is crucial for identifying areas of strength and potential improvement in school management practices. This research is quantitative and descriptive, with a population of 270 teachers. The sample size was determined using the Slovin formula, employing the Proportionate Random Sampling technique, resulting in a sample of 76 teachers. The research instrument used was validated and proven reliable. The results showed that teacher development and the improvement of learning quality were well-implemented, as were effective school management and the creation of a positive school culture. Continuous monitoring and evaluation were also found to be effectively implemented. The overall results indicate that teachers have a positive perception of the leadership of the driving principal, with an average score of 4.3, suggesting that the leadership approach is being carried out effectively across all evaluated areas.